Promosi kesehatan menggunakan gambar dan teks dalam aplikasi WhatsApp pada kader posbindu - Nopryan Ekadinata; Doni Widyandana (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
PurposeThis study aimed to determine the effectiveness of educational programs through WhatsApp media on the level of knowledge and satisfaction of learning of Posbindu health workers.Methods This study was an experimental research on 1 group that consisted of 33 respondents. Two stages of intervention were done with sending an educational text message about diabetes in the first week and picture messages in the second week. The instruments of this study consisted of a knowledge questionnaire and a learning satisfaction questionnaire. The study was conducted on Posbindu health workers with message delivery interventions through WhatsApp.ResultsThere was a significant change between the mean pre-test and post intervention of text messaging and educational images on knowledge of type 2 diabetes variables, while the delivery of picture messages had the highest mean value of learning satisfaction.Conclusions Promotion and health education programs through message delivery on WhatsApp effectively can improve the knowledge and satisfaction of learning about type 2 diabetes mellitus.